Doctoral Dissertations in Economics One-Hundred-Fifth Annual List (Journal of Economic Literature, 2008)
The list below specifies doctoral degrees conferred by U.S. and Canadian universities during academic year July 2007 to June 2008. Lists of degree recipients and subject classifications are provided by the university. Note: Dissertations without classifications may be found under “Y Miscellaneous Categories.”